B(C6F5)3‐Enabled Synthesis of a Cyclic cis‐Arsaphosphene. Issue 21 (27th March 2019) - Mehta, Meera; McGrady, John E.; Goicoechea, Jose M.
Abstract: The synthesis and characterization of an (arsino)phosphaketene, As(PCO)[N(Dipp)](CH2 )2 (Dipp=2, 6‐diisopropylphenyl) is reported along with its subsequent reactivity with B(C6 F5 )3 . When reacted in a stoichiometric ratio, B(C6 F5 )3 drove the insertion of the P=C bond of the phosphaketene into one of the As−N bonds of the arsino functionality, affording an acid‐stabilized, seven‐membered, cyclic arsaphosphene. In contrast, when catalytic amounts of B(C6 F5 )3 were employed, dimeric species, which formed through a formal [2+2] cycloaddition of the cyclic arsaphosphene, were generated. The cyclic arsaphosphene product represents the first example of such a compound in which the two substituents are arranged in a cis ‐configuration. Abstract : Reagent and promoter : Stoichiometric and catalytic reactions between B(C6 F5 )3 and an (arsino)phosphaketene, [As(PCO)[N(Dipp)](CH2 )2 ] (Dipp=2, 6‐diisopropylphenyl) are reported. In a stoichiometric ratio, an acid‐stabilized, cyclic cis ‐arsaphosphene was isolated. In contrast, when catalytic amounts of B(C6 F5 )3 were employed, dimeric species, which form through a formal [2+2] cycloaddition of the cyclic arsaphosphene, were generated.